PENDAMPINGAN GURU DALAM PENULISAN LAPORAN JURNAL PENELITIAN TINDAKAN KELAS KOLABORATIF - Syahdan Syahdan; Herlinawati Herlinawati; Syaifullah Syaifullah (Unika Santu Paulus Ruteng, 2022)
Research publications made by teachers, especially in Riau Province, are not comparable to provinces in Java Island. Therefore, this community service aimed at providing training on the basic concepts of collaborative classroom action research (CAR) and assistance in writing collaborative CAR from which the papers are expected to be published in accredited national journals. This activity was targeted to teachers at SMA Negeri 6 Tualang. The school was chosen due to its status as Sekolah Penggerak (literally translated as school mover). In addition, the teachers’ ability in carrying out collaborative CAR and writing for publication were not good. The training on basic concept of CAR included problem identification, problem formulation, choosing the right strategy, making observation sheets, and making field notes. To achieve the goal of publication, the teachers were assisted by students who were conducting teaching practice. They were active to consult with the team of community service at the Faculty of Teacher Training and Education, Universitas Lancang Kuning. The results obtained from this activity were an increase in the teacher's understanding of the basic concepts of CAR, how to identify problems, how to formulate problems, choose the right strategy, techniques for making observation sheets, and techniques for making field notes. Meanwhile, in the CAR activities, the teachers have accomplished the procedures well. More importantly, some of them have completed the initial section (Introduction) and are in the progress of making the other sections, namely Research Methods, Findings and Discussion, and Conclusion of their articles. Thus, it can be concluded that this CAR writing assistance activities have been carried out successfully.